#TITLE_ALTERNATIVE# - Tandi Seno NIM. 23299516, Titus
Abstract: This thesis applies Adaptive neuro-fuzzy method to evaluate peak load estimatiom of short-term at PT. PLN (Persero) UPB 150kV-70 kV Cigelereng Bandung West Java. The simulation was done by comparing four kinds of training data. i. e., 6 months, 12 months, 18 months and 24 months. The best results of the four of data training will be compared to statistic method, which are regression analysis, and average method. MATLAB version 5.31 and Microsoft Exceel do the software of this estimation. The final result shown that peak load estimation with applies adaptive neuro-fuzzy method for 12 months data set training give the best estimation result.